Keefektivan Metarhizium anisopliae Sebagai Agen Pengendali Hayati Terhadap Larva Lalat Musca domestica L. - Muhammad Amiruddin; Umrah Umrah; Muhammad Alwi (Biocelebes, 2012)
Research on the "effectiveness of the fungus Metarhizium anisopliae as a biological control agent against the larvae of the fly Musca domestica (L)” was done and focusingin determination of the effectiveness of this fungus as a biological control agent against Musca domestica larvae and to determine LC (Lethal Concentration) 50 and LC 90 on this biological control proceses. This study was designed in a completely randomized design consisting of 6 treatments and 3 replications. Arrangement of treatments i.e. the concentration of M. anisopliae in distilled water was; Po = distilled water without spore suspension, P1 = 5.1 × 1010 spores / mL, P2 = 2.0 × 1010 spores / mL, P3 = 1.0 × 1010 spores / mL, P4 = 5.1 × 109 spores / mL, and P5 = 2.0 × 109 spores / mL. Based on the observations, the mortality percentage rate was reached 93.33% as it in the treatment of spora concentration of 5.1 x1010 spores / mL.Probit analysis showed that LC50 was 8.3 x109 spores / mL with the range between the lower limit and the upper limit were 6.24 x109 spores / mL -11.43 x109 spores / mL. While the LC 90 was 5.0 x1010 spores / mL with the range of the lower limit until the upper limit were 2.8 x1010 spores / mL - 9.9 x1011 spores / mL. Key words: Metarhizium anisopliae, Musca domestica, effectiveness, mortality, biological control